PENYELENGGARAAN PELAYANAN ADMINISTRASI TERPADU KECAMATAN (PATEN) DI KABUPATEN TEMANGGUNG - Nabilah Hanim; Kushandajani Kushandajani; Ahmad Taufiq (Journal of Politic and Government Studies, 2015)
Public service is one way to achieve general welfare. The implementation of public services effectively and efficiently is something that is expected by the public. Because today is the quality of public services in Indonesia is still far from good. In order to create a public service that is effective and efficient, the government made the Integrated Administrative Service District (PATEN).The aim of the study is to examine how the implementation of the Integrated Administrative Service District (PATEN) in Temanggung Regency, and identify factors inhibiting the implementation and to know the efforts that have been made by the government to improve the quality of the PATEN. This study uses a descriptive qualitative research method. Triangulation of data or sources technique is used in this study to obtain a data validity. Data collected by field research and interviews with relevant parties. This research was carried out at Temanggung Regency.Results of this study describe the implementation of the Integrated Administrative Service District (PATEN) which can be seen from the substantive requirements, administrative and technical, the type of services provided and the flow of services, financing, human resources, as well as the completeness of infrastructure and facilities. In its implementation found that inhibiting factors internal and external factors. In addition, it was found that several attempts have been made to improve the quality of the PATEN. Recommendations are given, the expected the implementation of the Integrated Administrative Service District (PATEN) in Temanggung Regency work effectively and efficiently.